KESANTUNAN TINDAK TUTUR DIREKTIF ANGGOTA DPRD - Syafruddin Syafruddin; Siti Suwadah Rimang (Fakultas Sastra Universitas Negeri Malang, 2014)
Gentle, polite, courteous, systematic, organized, clear, and straight forward use of language reflects a speaker’s personality and culture. Everyone, including the members of the South Sulawesi Parliament, is expected to maintain good manner and ethic in communication. The study aims to describe and explain declarative, interrogative, and imperative forms as well as speech act strategies used by the members the South Sulawesi Parliament. The qualitative study employed the functional approach on language. The study was conducted in the South Sulawesi Parliament House. The data of the research were obtained from speech acts, field observations and interviews. The stages of data collection are 1. Preparation, 2. Recording, 3. Observation, 4. Interview, and 5. Transcription. The data were analyzed by the following procedures: 1. data reduction, 2. data presentation and interpretation, and, 3. data conclusion and verification. The findings revealed that there were various forms of politeness used by the respondent. Moreover, the locution act was the more dominant strategy used by the respondent than the illocutionary act.